Mechanical behaviour of Kevlar fibre matrix composites manufactured through hand-lay process - V. Mohanavel,; D.Muralidharan,; G.Mukeshkumar,; S.Sivaraj, (International Journal of Psychosocial Rehabilitation, 2020)
In the current days, composite serve as a essential role in the aircraft, structural automotive, marine and electronics and so on. Composite are being employed in the aircraft to obtain much efficiency. The main benefits of our experimental work is to augment the impact resistance, hardness and strength-weight ratio of the material which is going to be produced through the combination of Kevlar (K) and Nylon (N), E-glass (EG) fibers using pairing method. The fabrication of the polymer matrix composite is done by conventional hand-lay (CH) approach. Polyester (SKR 2501) resin alongside with HY951 hardener is used as the binding element throughout the layer. This experimental work deals with producing, mechanical characterization of a hybrid (K+N+K) composite and also the comparison of it with the (EG+K+EG) based composite. Experimental outcome reveals the hybrid synthetic composite has outstanding properties under impact and tensile loading.